2007
DOI: 10.1111/j.1525-1438.2007.00941.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors associated with brain metastases from epithelial ovarian carcinoma

Abstract: Brain metastasis from epithelial ovarian carcinoma (EOC) is managed by a multimodal treatment approach. Thus, to determine the prognostic factors associated with this situation is important for management decisions regarding the type of treatment and aggressiveness of treatment. From 1995 to 2005, 13 patients with brain metastases resulting from EOC underwent treatment at Samsung Medical Center. We retrospectively reviewed the medical records to determine prognostic factors and to evaluate treatment outcome. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 22 publications
4
41
0
Order By: Relevance
“…(Anupol, 2002;Brown III, 2005;Chen, 2009;Cohen, 2004;Cormio, 1995, 2003b, Cormio, 2011aD'Andrea, 2005;Kastritis, 2006;Kim, 2007;Kumar, 2003;Lee, 2008;Sanderson, 2002;Sehouli, 2010;Tay & Rajesh, 2005). However Kolomainen et al demonstrated in their series that a brain involvement could be seen quite frequently (one third of their patients) also in patients with FIGO stage I.…”
Section: Clinicopathological Characteristics Of the Primary Tumourmentioning
confidence: 97%
See 2 more Smart Citations
“…(Anupol, 2002;Brown III, 2005;Chen, 2009;Cohen, 2004;Cormio, 1995, 2003b, Cormio, 2011aD'Andrea, 2005;Kastritis, 2006;Kim, 2007;Kumar, 2003;Lee, 2008;Sanderson, 2002;Sehouli, 2010;Tay & Rajesh, 2005). However Kolomainen et al demonstrated in their series that a brain involvement could be seen quite frequently (one third of their patients) also in patients with FIGO stage I.…”
Section: Clinicopathological Characteristics Of the Primary Tumourmentioning
confidence: 97%
“…Although older studies suggested that these patients should undergone only palliative management, in the last 15 year's published studies many authors agree that a multi-modal treatment is the modality of choice in selected patients and can achieve a long-term remission and a better quality of life. (Anupol, 2002;Brown III, 2005;Chen, 2009;Cohen, 2004;Cormio, 1995;Cormio, 2003b;Cormio, 2011a;D'Andrea, 2005;Kastritis, 2006;Kim, 2007;Lee, 2008;Sanderson, 2002;Sehouli, 2010;Tay & Rajesh, 2005). An aggressive multimodal approach should be aimed both to cure local and systemic disease and leads to an improvement in duration and quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, patients with solitary metastases have undergone metastasectomy and whole brain radiotherapy (WBRT) [25]. The latter is associated with a number of late complications, including brain atrophy, necrosis, dementia, and endocrine dysfunction [26].…”
Section: Discussionmentioning
confidence: 99%
“…Contrast-enhanced magnetic resonance imaging (MRI) is the most accurate modality to image the brain [25].…”
Section: Discussionmentioning
confidence: 99%